Prolonged Anesthesia Induction to Delivery Time Did Not Influence Plasma Remifentanil Concentration in Neonates - Cai M; Liu H; Peng Y; Miao JK; Lei XF; Yu J (Dove Medical Press, 2023)
Meng Cai,1 Hao Liu,2 Yong Peng,2 Jing-Kun Miao,2 Xiao-Feng Lei,1 Jin Yu1 1Department of Anesthesiology, Chongqing Health Center for Women and Children, Women and Children's Hospital of Chongqing Medical University, Chongqing, People's Republic of China; 2Department of Pediatrics, Chongqing Health Center for Women and Children, Women and Children's Hospital of Chongqing Medical University, Chongqing, People's Republic of ChinaCorrespondence: Jin Yu, Department of Anesthesiology, Chongqing Health Center for Women and Children, Women and Children's Hospital of Chongqing Medical University, No. 120, Longshan Road, Yubei District, Chongqing, 401147, People's Republic of China, Tel +86-18623117820, Email dodoes@qq.comObjective: Remifentanil, in combination with etomidate and sevoflurane, is commonly used in clinics for general anesthesia induction in cesarean section (CS). This study aimed to evaluate the correlation between the induction to delivery (I-D) time and neonatal plasma drug concentration and anesthesia, as well as its effects on neonates.Methods: Fifty-two parturients in whom general anesthesia was induced for CS were divided into group A (I-D< 8 min) and group B (I-D≥ 8 min). Maternal arterial (MA), umbilical venous (UV), and umbilical arterial (UA) blood samples were collected at delivery to analyze the remifentanil and etomidate concentrations using liquid chromatography-tandem mass spectrometry.Results: There were no statistically significant differences between the two groups in terms of plasma concentrations of remifentanil in the MA, UA, and UV blood (P > 0.05). The plasma concentration of etomidate in MA and UV was higher in group A than that in group B (P< 0.05), whereas the UA/UV ratio of etomidate was higher in group B than that in group A (P< 0.05). The Spearman rank correlation test showed no correlation between the I-D time and plasma remifentanil concentration in the MA, UA, and UV plasma (P> 0.05). The concentrations of etomidate in the MA and UV were negatively correlated with the I-D time (P < 0.05).Conclusion: Prolonged I-D time did not significantly influence the maternal or neonatal plasma concentration of remifentanil. It is safe to administer remifentanil target-controlled infusion in combination with etomidate and sevoflurane for general anesthesia induction during CS.Keywords: cesarean section, placental transport, general anesthesia, remifentanil, etomidate, drug concentration